Reduced phosphorus is associated with older age and hypoalbuminemia. Risk factors for all-cause mortality in peritoneal dialysis patients - Ávila, Marcela; Prado, Ma. del Carmen; Cuevas-Budhart, Miguel Ángel; Paniagua, Ramón (Frontiers in Nutrition, 2023)
Introduction/Aim. Hyperphosphatemia is a mortality risk factor in dialysis patients; however, low phosphorous levels (P) too. Diabetes and malnutrition are strongly associated with mortality and with reduced serum phosphorous. This study analyzed the pattern of serum Phosphorous in patients on Peritoneal Dialysis (PD) and its association with mortality. Methods. A Secondary analysis was performed on a multicenter cohort study in peritoneal dialysis patients from two previous studies done by our group. Results. Six hundred fifty-four patients were included. Serum phosphorous was<3.6 mg/dL in 28.29% of patients, 3.6 to 5.2 mg/dL in 48.16%, and>5.2 mg/dL in 23.55%. In logistic regression analysis; education, age, and hypoalbuminemia were risk factors for low P levels. In multivariate Cox analysis P<3.6 mg/dL, age, and low albumin were predictors for all-cause mortality. When lower P and lower albumin were combined, this group had the highest risk for all cause and cardiovascular mortality. Conclusions. The frequency of patients with reduced serum phosphorous was higher in the Mexican population than in Europe or Asia. Low serum phosphorous levels, older age and hypoalbuminemia were risk factors for all-cause mortality. Low phosphorus combined with low albumin levels were the highest risk factor for all-cause and cardiovascular mortality.